Patient's quality of life after surgery and radiotherapy for extremity soft tissue sarcoma-a retrospective single-center study over ten years - Götzl, Rebekka; Sterzinger, Sebastian; Semrau, Sabine; Vassos, Nikolaos; Hohenberger, Werner; Grützmann, Robert; Agaimy, Abbas; Arkudas, Andreas; Horch, Raymund E.; Beier, Justus (Health and Quality of Life Outcomes, 2019)
Background and objectives: The purpose of this study is to analyze major complication rates and different aspects of health-related quality of life (HRQoL) in extremity soft tissue sarcoma (STS) patients treated with or without radio (chemo) therapy and surgery. Methods: We performed a retrospective analysis of all patients who underwent Extremity STS excision from 2004 to 2014 (182 patients included). Patients' data were collected from patients' records. HRQoL was assessed by using EORTC QLQ-C30. Results: A total of 182 patients underwent sarcoma resection. After neoadjuvant radiochemotherapy (RCT), the major-complication rate amounted to 28% (vs. 7%, no radiotherapy, p < 0.001). Major-complication rates after adjuvant radiotherapy (RT) occurred in 8% (vs. 7%, no radiotherapy, p = 0.265). Comparison QoL scores between treating with neoadjuvant RCT or without RT revealed significant worse scores with neoadjuvant RCT. Further stratification of disease control of these patients showed significant reduced scores in the group of disease-free patients with neoadjuvant RCT compared to irradiated disease-free patients. Discussion: To date, there have only been a few investigations of QoL in STS. Retrospective study on quality of life have limitations, like a lack of baseline evaluation of QoL. Patient candidated to radiation therapy could have had worse QoL baseline due to more advanced disease. Disease status of the patients who answered the questionnaires could have been an influence of QoL and we could show reduced scores in the group of disease-free patients with neoadjuvant RCT, but not for the patients with recurrence or metastasis, so it is very hard to discriminate whether radiation therapy could really have an impact or not. Conclusion: This study might assist in further improving the understanding of QoL in STS patients and may animate for prospective studies examining the oncological therapies impact on HRQoL.
CRIS-Team Scopus Importer:2019-11-19
Keywords: Health related quality of life; QLQ-C30; Sarcoma major complication rates; Sarcoma radiotherapy; Soft tissue sarcoma

The role of plastic reconstructive surgery in surgical therapy of soft tissue sarcomas - Götzl, Rebekka; Sterzinger, Sebastian; Arkudas, Andreas; Boos, Anja; Semrau, Sabine; Vassos, Nikolaos; Grützmann, Robert; Agaimy, Abbas; Hohenberger, Werner; Horch, Raymund E.; Beier, Justus (Cancers, 2020)
Background: Soft tissue sarcoma (STS) treatment is an interdisciplinary challenge. Along with radio(chemo)therapy, surgery plays the central role in STS treatment. Little is known about the impact of reconstructive surgery on STS, particularly whether reconstructive surgery enhances STS resection success with the usage of flaps. Here, we analyzed the 10-year experience at a university hospital’s Comprehensive Cancer Center, focusing on the role of reconstructive surgery. Methods: We performed a retrospective analysis of STS-patients over 10 years. We investigated patient demographics, diagnosis, surgical management, tissue/function reconstruction, complication rates, resection status, local recurrence and survival. Results: Analysis of 290 patients showed an association between clear surgical margin (R0) resections and higher-grade sarcoma in patients with free flaps. Major complications were lower with primary wound closure than with flaps. Comparison of reconstruction techniques showed no significant differences in complication rates. Wound healing was impaired in STS recurrence. The local recurrence risk was over two times higher with primary wound closure than with flaps. Conclusion: Defect reconstructions in STS are reliable and safe. Plastic surgeons should have a permanent place in interdisciplinary surgical STS treatment, with the full armamentarium of reconstruction methods.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Plastic surgery; Reconstruction; Reconstructive surgery; Soft tissue sarcoma; STS